Solvability of a Hadamard Fractional Boundary Value Problem at Resonance on Infinite Domain - Xingfang Feng; Yucheng Li (Journal of Function Spaces)
This paper investigates the existence of solutions for Hadamard fractional differential equations with integral boundary conditions at resonance on infinite domain. By constructing two suitable Banach spaces, establishing an appropriate compactness criterion, and defining appropriate projectors, we study an existence theorem upon the coincidence degree theory of Mawhin. An example is given to illustrate our main result.